2016
DOI: 10.3382/japr/pfw003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lysine and methionine supplementation on Ross 708 male broilers from 21 to 42 days of age (II): breast meat quality

Abstract: SUMMARYIn a previous companion study, we found that broiler growth performance and meat yield were improved by the feeding of increased levels of dietary lysine (Lys) and methionine (Met). In the current study, dietary Lys and Met supplementation were evaluated for their effect on the breast (pectoralis major) meat quality of male Ross × Ross 708 broilers. A completely randomized block design with a 2 × 4 factorial arrangement of treatments was applied (10 blocks and 8 treatments/block). The diets, including 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The chemical benefits of this natural product increased the carcass and breast yields at 32 days (T1) (at slaughter), perhaps due to better intestinal health and absorption of biomolecules in the gastrointestinal tract, as amino acids. An improvement in the absorption of lysine increases the yield of the breast (Zhai et al, 2016) and therefore the carcass yield, as was observed in our experiment.…”
Section: Effects Of Dietary Supplementation With Red Algae Powder (Chsupporting
confidence: 87%
“…The chemical benefits of this natural product increased the carcass and breast yields at 32 days (T1) (at slaughter), perhaps due to better intestinal health and absorption of biomolecules in the gastrointestinal tract, as amino acids. An improvement in the absorption of lysine increases the yield of the breast (Zhai et al, 2016) and therefore the carcass yield, as was observed in our experiment.…”
Section: Effects Of Dietary Supplementation With Red Algae Powder (Chsupporting
confidence: 87%
“…Furthermore, methionine in the rumen-protected form is considered to be capable of supporting protein synthesis and inhibiting protein degradation through involvement in the synthesis of reduced glutathione (GSH), which naturally inhibits reactive oxidative species (ROS) [3]. Besides, supplementation with lysine increased the concentration of sarcoplasmic protein, which positively correlates with an increase in meat tenderness [4]. Studies have inferred that when methionine and lysine are absorbed efficiently in the ruminant's small intestine, the animals retain more nitrogen and, consequently, the muscle fiber types and satellite cell populations and altered; these amino acids may serve as optimizing agents for growth rate and are critical for maximizing lean tissue deposition [5].…”
Section: Introductionmentioning
confidence: 99%
“…2) Area was measured from longissmus thoracis muscle. 4) A grade (yield index ≥ 69.00) = 3, B grade (66.00 ≤ yield index < 69.00) = 2, C grade (yield index < 66.00) = 1. 5) Marbling score standard; No.1-No.9 (1 = devoid, 9 = abundant).…”
mentioning
confidence: 99%
“…Studies with commercial broiler chickens (Faridi et al 2015), local breed of chickens (Nasr & Kheiri 2011;Yuan et al 2015), quails (Mehri et al 2013), turkeys (de Paula Dorigam et al 2016), White Pekin ducks (Xie et al 2009), and local Korean ducks (Wickramasuriya et al 2016) suggested increasing Lys levels to improve average daily gain, feed consumption, and feed efficiency. Moreover, carcass yield, breast meat yield, water-holding capacity, tenderness, and meat taste improved as a result of increasing Lys concentrations, whereas abdominal fat and cooking loss declined which led to enhance meat quality and consumer acceptance (Berri et al 2008;Watanabe et al 2015;Zhai et al 2016).…”
Section: Introductionmentioning
confidence: 99%